Electronic and Optical Properties of Metalloporphyrins of Zinc on tio2 Cluster in Dye-Sensitized Solar-Cells (Dssc). a Quantum Chemistry Study - Mera-Adasme, R (Royal Society of Chemistry, 2017)
Dye-sensitized solar-cell (DSSC) systems have been investigated by calculating light-absorption and electron-injection processes of the LD13 ([5,15-bis(2,6-(1,1-dimethylethyl)-phenyl)-10-4-dimethylaminophenylethynyl-20-4-carboxy phenylethynyl porphyrinato]zinc-(ii)) and YD2-o-C8 ([5,15-bis(2,6-dioctoxyphenyl)-10-(bis(4-hexylphenyl)amino-20-4-carboxyphenylethynyl)porphyrinato]zinc-(ii)) dyes adsorbed on a TiO2 cluster simulating the semiconductor. The binding energy of the dyes with the TiO2 clusters has been calculated at the density functional theory (DFT) level using the B3LYP and CAM-B3LYP functionals. The electronic excitation energies have been calculated at the time-dependent DFT (TDDFT) level for the dyes in the gas and solvent phase employing the B3LYP, CAM-B3LYP and BHLYP functionals. The calculated excitation energies have been compared to values obtained at the algebraic diagrammatic construction through second order (ADC(2)) level of theory. The TDDFT calculations with the B3LYP in tetrahydrofuran solvent with the dye and dye-TiO2 models yield excitation energies that agree well with the transitions in the experimental absorption spectra. Changes in the free energy for electron injection support the better performance of the dyes on the TiO2 clusters. © 2017 The Royal Society of Chemistry.